Karawitan Cultural Arts Oriented to the Philosophy of Love for Country for Students of Elementary School - Hartono; Ardy Wiyani, Novan (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Along with the development of the times, the issue of education in every country is not an easy issue. Learning for students of Madrasah Ibtidaiyah (MI) requires a fun learning system. Learning outside the classroom is chosen as a suitable learning technique for elementary school students. Learning activities outside the classroom for elementary school students include karawitan art which has a philosophy and purpose to foster love for the homeland. This is because of the diversity of languages, customs, and cultures that make Indonesia. The wealth of the country that should be maintained, preserved and should be proud of includes karawitan art and culture to foster an attitude of love for the homeland. The purpose of this study is to describe karawitan art and culture activities that are oriented towards the philosophy of love for the homeland for MI students. This type of research is qualitative research with the approach used is qualitative naturalistic, because the research was conducted in natural conditions. The results of the study indicate that learning outside the classroom of karawitan art oriented towards the philosophy of love for the homeland can be seen from the indicator that students are proud of karawitan art as an original Indonesian art and culture.